2006
DOI: 10.1111/j.1526-100x.2006.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulch on Seedlings and Soil on a Closed Landfill

Abstract: Landfills are ideal locations for short-rotation forestry, tree-based bioremediation, and wildlife habitat reconstruction. However, tree survival is reduced by harsh growing conditions and poor soil quality. This study was designed to determine survival of tree seedlings and test effects of different mulch types and depths on edaphic properties and herb emergence on a closed Ohio landfill. In spring 2002, five species of hardwood tree seedlings (Fraxinus pennsylvanica, Robinia pseudoacacia, Prunus serotina, Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…We put this down to the fact that slash mulching may well result in changes to soil properties that encourage above-ground biomass development. For example, higher soil humidity, greater provision of nutrients and smaller fluctuations in temperature at ground level have already been described in several studies (O'Connell et al 2004;Athy et al 2006;Fang et al 2007). In fact, in a semi-arid Mediterranean environment these abiotic factors are of crucial importance to the development of vegetation (Valladares 2004).…”
Section: Discussionmentioning
confidence: 82%
“…We put this down to the fact that slash mulching may well result in changes to soil properties that encourage above-ground biomass development. For example, higher soil humidity, greater provision of nutrients and smaller fluctuations in temperature at ground level have already been described in several studies (O'Connell et al 2004;Athy et al 2006;Fang et al 2007). In fact, in a semi-arid Mediterranean environment these abiotic factors are of crucial importance to the development of vegetation (Valladares 2004).…”
Section: Discussionmentioning
confidence: 82%
“…The main advantage of mulching is organic and nutrient supply (Głąb and Kulig, 2008). For example, an addition of a layer of 15 cm of leaf mulch can increase organic matter as well as phosphorus, magnesium and cation exchange capacity in the soil (Athy et al, 2006). The organic carbon, total nitrogen and available phosphorus content of soils can be increased with the addition of mulch (Gaur and Mukherjee, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Mulches protect soil from drying and baking effect that leads to less evaporation and optimum soil temperature. [2] reported that mulches increase soil fertility and microbial activity of the soil by adding valuable amount of organic carbon. In addition, mulches also decrease the fluctuations of temperature soil by providing coverage to the soil that helps to reduce evaporation from soil surface.…”
Section: Introductionmentioning
confidence: 99%